Editorial. Conference proceedings of the 1st Biennial International Conference for the Craft Sciences – BICCS 2021 - Groth, Camilla; Westerlund, Tina; Almevik, Gunnar (FormAkademisk, 2021)
The papers appearing in this issue comprise the proceedings of the 1st Biennial International Conference for the Craft Sciences, held online during 4–6 May 2021, initiated by the Craft Laboratory, affiliated at the Department of Conservation, University of Gothenburg, Sweden. The Craft Laboratory was established in 2010 in cooperation with heritage organisations, craft enterprises and trade organisations, to empower craftspeople in the complex processes of making. The comprehensive agenda is to bring research into practice and involve craftspeople in the processes of inquiry. Among the operational tools are Master Classes provided for highly trained professional craftspeople in particular skills. Craft Scholarships are offered to craftspeople to investigate a problem or question in their practice, or develop ideas to improve methods or techniques. The site-specific workshop capacity in Mariestad allows craft researchers to implement research questions in practice and to perform full-scale tests in our masonry, carpentry and painting workshops, as well as in the timber building yard, greenhouses and gardens.